A proteção da biodiversidade marinha da Ilha de Ataúro, Timor-Leste - Madeira, Helena Pereira (2020)
Timor-Leste is one of six countries of the Coral Triangle Region. Several studies show that its seas have the largest maritime biodiversity in the world, particularly the waters around Ataúro island. In order for these resources to contribute to the national economy, a preservation analysis is required that only protect areas can allow. About 90 % of the economy of Timor-Leste depends on the revenues of the oil industry. Timor- Leste is the second most dependent country in the world on oil, and its reserves are rapidly ending. This means it is necessary to establish policies of economic diversification, and to look for new economic industries with more sustainable capacity for growth. The creation of the marine protected area (MPA) is regarded as an adequate tool to protect maritime biodiversity, species and habitats, endangered ecosystems and ecological processes. This is true for the coastal areas as well as in the deep ocean. The assurance of the long-term sustainability of the MPA’s will greatly depend of the ability and resources (human, financial and material or technological). The collaboration between the public entities, the private sector, the civil society, non-governmental organizations and local communities also plays a crucial role. This work aims at finding the adequate public policies for the conservation and protection of the maritime natural resources and the environment of Timor-Leste. It also analyzes two important subsectors for the substitution of oil revenues, namely Tourism and Fishing. According to the literature, as well from the practice of other countries, these subsectors are key to generate profits from the sea, both greatly benefiting with the creation and management of MPA’s. If well managed and exploited, it is expected they can contribute to the economic growth of the country and the well-being of the Timorese people, especially in the island of Ataúro. Furthermore, the obstacles and challenges to the achievement of the goals set in the strategic plan for national development, particularly regarding the sea, will also be discussed.